(untitled) (PANGEEA, 2025)
Solar energy is a resource increasingly used worldwide, being the fastest growing energy source in recent years. It is estimated that the world’s technical potential for solar energy can provide five times more energy than it is consumed now. With regard to the solar potential of our country, Romania benefits from the highest potential in South-Eastern Europe.